2022
DOI: 10.17969/agripet.v22i2.23423
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation The Success of Artificial Insemination Using Frozen Sexed Semen Based on Different Estrus Characters

Abstract: ABSTRACT. Knowledge of farmers about estrus detection is one of the factors that affect fixed-time artificial insemination (AI). This study aims to evaluate the success rate of AI using Y sexing frozen semen based on the estrus character of cattle. Forty-five Limousin Crossed Cows involved in this research with a Body Condition Score of 3-5 (1-9 scale), 1.8-7 years old. Y sexing frozen semen is produced by the Singosari Center for Artificial Insemination using Percoll's Gradient Density Centrifugation method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Cases in Woha sub-district, Bima regency, West Nusa Tenggara province was 4.55% (Lukman et al, 2023), 10-40% in dairy farms (Lee et al, 2021), 19% in Tutur district, Pasuruan regency (Qodri et al, 2020. First ovulation in cows generally occurred silently (i.e., no estrus behavior) and was generally (>70%) followed by a short cycle (Utami et al, 2022). In this study, it was confirmed that some cows with SE at a young age (two to three years old, heifers or first parities).…”
Section: Silent Estrussupporting
confidence: 73%
See 2 more Smart Citations
“…Cases in Woha sub-district, Bima regency, West Nusa Tenggara province was 4.55% (Lukman et al, 2023), 10-40% in dairy farms (Lee et al, 2021), 19% in Tutur district, Pasuruan regency (Qodri et al, 2020. First ovulation in cows generally occurred silently (i.e., no estrus behavior) and was generally (>70%) followed by a short cycle (Utami et al, 2022). In this study, it was confirmed that some cows with SE at a young age (two to three years old, heifers or first parities).…”
Section: Silent Estrussupporting
confidence: 73%
“…Silent estrus could be caused by disruption of ovarian activity due to low consumption of nutrients in feed. Lack of nutrition caused endocrine disorders in the hypothalamus-pituitary-ovary axis, which was followed by low estrogen levels so that cows could not show signs of estrus (Utami et al, 2022). In this study, the highest number of SE cases occurred mostly in cows fed dry straw.…”
Section: Silent Estrusmentioning
confidence: 58%
See 1 more Smart Citation
“…One of the factors that can affect the success rate of artificial insemination is the physiological condition of livestock, such as the condition of cows in responding to the environment and adapting Utami et al [26]. Acceptors in this study had Limousin blood, a Bos Taurus cattle originating from hot areas.…”
Section: Discussionmentioning
confidence: 86%